Prevalence of anxiety among women attending a primary care clinic in Malaysia. - Mohd Sidik, Sherina; Arroll, Bruce; Goodyear-Smith, Felicity (Royal College of General Practitioners, 2011)
Background: This is the first study investigating anxiety among women attending a primary care clinic in Malaysia. Aim: The objective was to determine the factors associated with anxiety among these women. Design: This cross-sectional study was conducted in a government-funded primary care clinic in Malaysia. Consecutive female patients attending the clinic during the data-collection period were invited to participate in the study. Method: Participants were given self-administered questionnaires, which included the validated Generalised Anxiety Disorder-7 questionnaire (GAD-7) Malay version to detect anxiety. Results: Of the 1023 patients who were invited, 895 agreed to participate (response rate 87.5%). The prevalence of anxiety in this study was 7.8%, based on the GAD-7 (score ≥8). Multiple logistic regression analysis found that certain stressful life events and the emotional aspect of domestic violence were significantly associated with anxiety (P<0.05). Conclusion: The prevalence of anxiety among women in this study is similar to that found in other countries. Factors found to be associated with anxiety, especially issues on domestic violence, need to be addressed and managed appropriately.